In Vitro Activity of 39 Antimicrobial Agents Against Treponema hyodysenteriae - Kitai, Kazuhisa (1979)
The in vitro activities of 39 antimicrobial agents against 23 isolates of Treponema hyodysenteriae, the majority of which were field isolates, were determined by the agar dilution technique. Quinoxalines, pleuromutilin, nitroimidazoles, and nitrofuran were the most active. Their activities ranged from ≤0.10 to 1.56 μg/ml. Lincomycin, penicillins, chloramphenicol, tetracyclines, cephalosporins, three peptides (virginiamycin, thiopeptin, and bacitracin), and one aminoglycoside (gentamicin) exhibited intermediate levels of activity ranging from 0.39 to 50 μg/ml. Four peptides (enduracidin, viomycin, bicyclomycin, and colistin), three aminoglycosides (kanamycin, streptomycin, and neomycin), polyene, and other agents, including novobiocin, vancomycin, rifampin, nalidixic acid, and p-arsanilic acid, displayed limited activities ranging from 12.5 to ≥100 μg/ml. Macrolides showed varying degrees of activity depending upon isolates.